Newly recorded ant-parasitizing genus (Diptera, Phoridae) from China, with descriptions of two new species - Liu, Guang-Chun (Zootaxa, 2022)
The ant-parasitizing genus Microselia Schmitz, 1934 is reported for the first time from China. Two new species, M. longarista sp. nov., M. yanjingensis sp. nov. are described and illustrated.